The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1159/000171502
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant Hepatic Failure Secondary to Previously Unrecognized Cardiomyopathy

Abstract: Fulminant hepatic failure is infrequently seen as a consequence of acute congestive heart failure. Recognition of this entity is important as treatment directed towards heart failure should help resolve the liver failure. A case of fulminant hepatic failure due to previously unrecognized cardiomyopathy is presented. A liver transplantation was being considered for fulminant hepatic failure until hemodynamic monitoring studies demonstrated that, in fact, the patient had severe cardiomyopathy. Treatment directed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…Only Kubo et al [9] reported a slight AST elevation (65 ± 82 U/L) in patients with a CI ≤ 1.5 L/min/m 2 . However, most other reports (Wiesen et al [18]; Fussell et al [4]) support the findings of our present study, where AST concentrations were shown to be elevated more than 2000-fold, despite a mean CI of 1.9 L/min/m 2 . The main difference of Kubo's report and the other studies are that Kubo described the incidence and severity of liver function abnormalities in patients with congestive heart failure, but in absence of acute decompensation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Only Kubo et al [9] reported a slight AST elevation (65 ± 82 U/L) in patients with a CI ≤ 1.5 L/min/m 2 . However, most other reports (Wiesen et al [18]; Fussell et al [4]) support the findings of our present study, where AST concentrations were shown to be elevated more than 2000-fold, despite a mean CI of 1.9 L/min/m 2 . The main difference of Kubo's report and the other studies are that Kubo described the incidence and severity of liver function abnormalities in patients with congestive heart failure, but in absence of acute decompensation.…”
Section: Discussionsupporting
confidence: 90%
“…Cardiomyopathy as the underlying cause of ALF is rare and only a few case reports are documented in the literature [5,7,8,18]. Cardiac decompensation can initially be undetected, and the usual signs of congestive heart failure may be absent [5,18]. Both, chronic and acute congestive heart failure can lead to hepatic dysfunction [10,17].…”
Section: Introductionmentioning
confidence: 99%
“…The cardiomyopathy can initially go undetected, and the usual signs of congestive heart failure may be absent (1,2). To our knowledge, no case of fulminant hepatic failure has been reported due to cardiomyopathy developing in the peripartum period.…”
Section: Discussionmentioning
confidence: 90%
“…Cardiomyopathy as the underlying cause of fulminant hepatic failure is rare, with only a few case reports documented in the literature (1)(2)(3)(4). The cardiomyopathy can initially go undetected, and the usual signs of congestive heart failure may be absent (1,2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation